2023
DOI: 10.4103/1673-5374.380874
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cells promote neuroplasticity: a promising therapeutic strategy for the treatment of Alzheimer’s disease

Abstract: Recent studies have demonstrated that neuroplasticity, such as synaptic plasticity and neurogenesis, exists throughout the normal lifespan but declines with age and is significantly impaired in individuals with Alzheimer’s disease. Hence, promoting neuroplasticity may represent an effective strategy with which Alzheimer’s disease can be alleviated. Due to their significant ability to self-renew, differentiate, and migrate, neural stem cells play an essential role in reversing synaptic and neuronal damage, redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 128 publications
0
5
0
Order By: Relevance
“…17,18 Recent studies have found that, impaired plasticity of hippocampal neurons contributes to the pathogenesis of depression. 4 CUMS lead to impairment of plasticity of hippocampal neurons and depressive-like behaviours in animal models, 5,18,19 hence promoting hippocampal neuroplasticity improved CUMS-induced depressive-like mood. 18 PSD-95 and SYP are important markers of neuroplasticity in the HIPP.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…17,18 Recent studies have found that, impaired plasticity of hippocampal neurons contributes to the pathogenesis of depression. 4 CUMS lead to impairment of plasticity of hippocampal neurons and depressive-like behaviours in animal models, 5,18,19 hence promoting hippocampal neuroplasticity improved CUMS-induced depressive-like mood. 18 PSD-95 and SYP are important markers of neuroplasticity in the HIPP.…”
Section: Discussionmentioning
confidence: 97%
“…3 Pathogenesis of depression is closely associated with impaired plasticity of hippocampal neurons. 4 Hence, modulating plasticity of hippocampal neurons may be a novel method to improve depression. In this paper, we planned to establish a rat model of depression by subjecting it to chronic unpredictable mild stress (CUMS), so as to investigate the effects of BEO on depressive-like behaviours and hippocampal neuroplasticity in CUMS-induced rats.…”
mentioning
confidence: 99%
“…This suggested that SHR rats have impaired neuronal myelin development, which may be involved in the development of ADHD. Neural stem cells (NSCs) can self-renew and provide new neurons to the brain tissue ( Chang et al, 2024 ). Thus, endogenous NSCs could potentially be used for brain repair.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell therapy has shown efficacy in enhancing memory and cognitive functions in animal models of AD, with extensive preclinical research dedicated to elucidating the mechanisms involved ( Chang et al, 2024 ; Temple, 2023 ). Transplanted bone marrow-derived mesenchymal stem cells (BMMSCs) stimulate neurogenesis and inhibit apoptosis, regulated by crosstalk between apoptosis and autophagy ( Qin et al, 2021a ).…”
Section: Targeting Autophagy In the Treatment Of Ad Modelsmentioning
confidence: 99%